Data Compression Conference
DOI: 10.1109/dcc.2005.33
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Source Coding in Dense Sensor Networks

Abstract: We study the problem of the reconstruction of a Gaussian field defined in [0, 1] using N sensors deployed at regular intervals. The goal is to quantify the total data rate required for the reconstruction of the field with a given mean square distortion. We consider a class of two-stage mechanisms which a) send information to allow the reconstruction of the sensor's samples within sufficient accuracy, and then b) use these reconstructions to estimate the entire field. To implement the first stage, the heavy cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
37
0

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…We are interested in the performance in the information-theoretic sense and, hence, we allow the delay to be arbitrarily large. By the assumption of sum power constraint, we have (8) The collector node reconstructs the random process as (9) For fixed encoding functions of the nodes and the decoding function of the collector node , the achieved expected distortion is (10) and we are interested in the smallest achievable expected distortion over all encoding and decoding functions where is allowed to be arbitrarily large.…”
Section: System Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…We are interested in the performance in the information-theoretic sense and, hence, we allow the delay to be arbitrarily large. By the assumption of sum power constraint, we have (8) The collector node reconstructs the random process as (9) For fixed encoding functions of the nodes and the decoding function of the collector node , the achieved expected distortion is (10) and we are interested in the smallest achievable expected distortion over all encoding and decoding functions where is allowed to be arbitrarily large.…”
Section: System Modelmentioning
confidence: 99%
“…Kashyap et al [8] studied the source coding part of the problem investigated in this paper. The paper showed that for any distortion constraint that is independent of , the difference between the rate achievable by distributed source coding and the rate achievable by centralized source coding is bounded by a constant, independent of .…”
mentioning
confidence: 99%
See 3 more Smart Citations